STRATEGI KEHIDUPAN KELUARGA LONG DISTANCE RELATIONSHIP (LDR) DALAM MEWUJUDKAN KELUARGA SAKINAH - Arif Hariyanto; Tengku Muhamad Mudawali J.A (Fakultas Syariah dan Ekonomi Islam, Universitas Ibrahimy, 2023)
Humans are creatures that cannot live individually. Definitely need help from other people in living a life. One proof of the truth of this statement is the presence of marriage. Marriage is a path taken by men and women who love each other and have a strong desire to create a family. A sakinah, mawaddah and rahmah family is of course the goal of all married couples, and this cannot be achieved without cooperation between husband and wife in the form of fulfilling the rights and obligations between the two which are based on equality, balance and justice. Based on the explanation above, it is important to have effective communication, in undergoing a husband and wife relationship, especially for husband and wife who are far apart, which is popularly known as Long Distance Relationship (LDR) or Long Distance Marital in Relationship. Frequently communicating effectively can be a joy for a husband and wife because they have not met for a long time, but on the other hand, the lack of effective communication between the two can cause problems in the family which will end in divorce